Determination of extended substrate specificity of the MALT1 as a strategy for the design of potent substrates and activity-based probes. Issue 1 (December 2018) - Kasperkiewicz, Paulina; Kołt, Sonia; Janiszewski, Tomasz; Groborz, Katarzyna; Poręba, Marcin; Snipas, Scott; Salvesen, Guy; Drąg, Marcin
Abstract Mucosa-associated lymphoid tissue lymphoma translocation protein 1 (MALT1) belongs to the CD clan of cysteine proteases. MALT1 is a unique enzyme among this clan because it recognizes the basic amino acid arginine in the P1 pocket. Previous studies carried out with natural amino acids revealed the substrate specificity of the P4-P1 pockets of MALT1 but have provided only limited information about the catalytic preferences of this enzyme. In this study, we exploited Hybrid Combinatorial Substrate Library and Internally Quenched Fluorescence substrate technologies to interrogate the extended substrate specificity profile of the S5-S2' active site pockets using unnatural amino acids. This strategy resulted in the design of a peptide-based fluorogenic substrate, which exhibited significant activity toward MALT1. Subsequently, the substrate sequence was further utilized to develop potent, irreversible activity-based probes.